The impact of density, temperature, moisture, and test direction on the thermal conductivity coefficient in pine wood - Trochonowicz, Maciej; Szostak, Bartosz (Budownictwo i Architektura / Civil and Architectural Engineering, 2023)
The article focuses on the study of the thermal properties of pine wood, a material traditionally used in construction, especially in Poland. The trend towards sustainable construction necessitates a deeper analysis of its properties. Due to the insufficient amount of data in the literature on the thermal conductivity of pine wood, detailed studies were conducted, taking into account different wood densities. Seasoned wood samples were subjected to various processes and tests, measuring the heat conduction coefficient under different conditions. These results are relevant in the context of sustainable construction and will assist in further research on wood as a building material. The studies also took into account the effects of temperature and humidity on the thermal properties of wood, which are crucial for its application in various environmental conditions.